TELAAH KRITIS TERHADAP PEMENUHAN HAK-HAK KORBAN PENIPUAN JUAL BELI ONLINE - Sri Setia Wati; Satria Aldi; Shofwatul Islamia Az-Zahra; Muh. Ramdan Yulia Saputra; Arwan (LPPM STISIP Persada Bunda, 2023)
The purpose of this study is to examine what are the victimizing factors in the occurrence of victimization and re-victimization of online buying and selling fraud, the implementation of Law Number 8 of 1999 concerning Consumer Protection and the government's efforts to deal with and overcome criminal acts of online buying and selling fraud. By using empirical legal research methods and conceptual approaches related to victimological theories, namely the theory of critical victimology. Focus on critical victimology theory to examine further the Victimization and Revictimization of Purchase and Purchase Fraud through Mass Media and E-Commerce. Based on this, it is obtained several factors that underlie the re-victimization of consumers as victims of online buying and selling fraud, namely, first, Media Platform Factors, such as Instagram and Facebook as marketplace promotion places that do not filter advertisements that can cause potential victims to arise. Second, the Law Enforcement Factor, blaming the victim and ignoring and asking for compensation for resolving the victim's case. There are several factors that cause victimization in buying and selling online including; sellers offer low prices through promotions, marketplace descriptions do not match reality, items purchased are only available on certain platforms, platforms are not/still ineffective in trying to cross-check seller credibility when registering to become sellers or when already becoming sellers, the police do not processing online fraudsters so that online fraudsters thrive, reporting online fraud requires a sizable fee.